1994
DOI: 10.1002/jsfa.2740640120
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and fate of dietary (U‐14C)‐labelled spinach cell walls in the rat

Abstract: Using uniformly '4C-labelled spinach (Spinacia oleracea L) plant cell walls (PCW) the metabolism of PCW can be followed in a defined manner in the rat. Only 10% of the I4C was recoverable in the gut contents and faeces 18 h post-gavage. Two percent of the I4C was excreted in urine and 25% excreted as CO, . I4C was found in all tissues of the body but was most concentrated in the adrenal glands, colon and caecum. The I4C was also present at moderately high concentration in the liver pelt, and owing to their lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
1996
1996

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The main differences between the metabolism of the 14C-PCW preparations may have occurred prior to the 18 h cessation of the experiment leaving a residue of labelled phospholipid. Previous studies have shown that (U-'4C)-labelled PCW contribute precursors to the biosynthesis of phospholipids, cholesterol esters and amino acids (Buchanan et al 1994). In the pelt of rats fed [methyl-'4C]pectin-labelled PCW the label was present as fatty acid esterfield to cholesterol and as amino acid, whereas in the pelt from rats fed [~ronate-6-'~C]pectin-labelled PCW the label was present only as amino acid residues.…”
Section: Discussionmentioning
confidence: 90%
“…The main differences between the metabolism of the 14C-PCW preparations may have occurred prior to the 18 h cessation of the experiment leaving a residue of labelled phospholipid. Previous studies have shown that (U-'4C)-labelled PCW contribute precursors to the biosynthesis of phospholipids, cholesterol esters and amino acids (Buchanan et al 1994). In the pelt of rats fed [methyl-'4C]pectin-labelled PCW the label was present as fatty acid esterfield to cholesterol and as amino acid, whereas in the pelt from rats fed [~ronate-6-'~C]pectin-labelled PCW the label was present only as amino acid residues.…”
Section: Discussionmentioning
confidence: 90%
“…The substitution of gelatinized (glucose) for retrograded starch (SCFAs) significantly increased the labeling in the adrenal glands during the early-absorptive period, and in the carcass, liver, and pelt, 18 h postgavage (Tables 6 and 8). A high incorporation of radioactivity into liver and pelt tissues has been also shown by Buchanan et al (1994) using uniformly 14 Clabeled spinach plant cell walls as fermentation substrate. (c, d), and between starches at 3 (R, ) and 18 (γ, δ) h, denotes significant differences (p < 0.05).…”
Section: Degradation Of [ 14 C]starch and Metabolism Of [ 14 C]starchmentioning
confidence: 80%
“…The pelt was highly labelled (12-15% of intake), and the radioactivity was shown to be entirely associated with the insoluble fraction. Alkalinehydrolysis of the rat pelt chloroform-insoluble material revealed that the label was predominantly present as non-essential amino acids such as aspartic acid, asparagine, glutamic acid and alanine (Buchanan et al 1994~).…”
Section: Digestion O F Uronate-6-'4c-labelled C E L L Walls In T H E mentioning
confidence: 99%